HEAR - Andreas Philippopoulos-Mihalopoulos, Danilo Mandic, Caterina Nirta, Andrea Pavoni (University of Westminster Press, 2023)
Hearing is an intricate but delicate modality of sensory perception, continuously enfolded in the surroundings in which it takes place. While passive in its disposition, it is integral to the movement and fluctuations of one's environment. Always attuned to the present and immersed in the murmur of its background, hearing remains a situated perception but fundamentally overarching and extended into the open. It is an immanent modality of being in and with the world. It is also the ultimate juridical act, a sense-making activity that adjudicates and informs the spatio-temporal acoustics of law and justice. This collection gathers multidisciplinary contributions on the relationship between law and hearing, the human vocalisations and non-human echolocations, the spatial and temporal conditions in which hearing takes place, as well as the forms of order and control that listening entails. Contributors explore, challenge and expand the structural and sensorial qualities of law, and recognise how hearing directs us to perceiving and understanding the intrinsic acoustic sphere of simultaneous relations, which challenge and break the normative distinctions that law informs and maintains. In exploring the ambiguous, indefinable and unembodied nature of hearing, as well as its objects – sound and silence – this volume approaches it as both an ontological and epistemological device to think with and about law.